THE ROLE OF MAGNETIC RESONANCE IMAGING WITH DYNAMIC SUBTRACTION IN DETERMINING LIVER LESIONS WITH CIRRHOSIS - (:unkn) unknown (GUNES KITABEVI LTD STI, 2013)
Introduction: The aim of this study is to evaluate the role of the Magnetic Resonance Imaging (MRI) with Dynamic Subtraction in determining liver lesions with cirrhosis. Materials and Method: We investigated the presence of lesions in the liver with standard MRI protocol among 30 patients with cirrhosis. Subsequently, subtraction process was applied to the dynamic images. Images obtained with standard and subtraction methods were analyzed; and the sensitivity, specificity, positive and negative predictive values were investigated. Results: The age range was 45-86, the average age was 65.6 and the median age was 64.5 years. On standard and subtraction images, no lesion was found in 14 patients. In 16 patients, after evaluation with standard protocol, 20 lesions were found. On dynamic images, 21 lesions were identified. When compared to standard protocol, with dynamic subtraction imaging, sensitivity to detect a lesion was found as 95.5%, whereas specificity was 87.5%, positive predictive value was 90.5%, negative predictive value was 93.3% and the accuracy was 91.6%. Conclusion: In the identification of the number of liver lesions, subtraction imaging was not superior to the standard protocole alone. However, the addition of subtraction images on the standard protocol improves the evaluation quality for lesions detected in cirrhotic liver.
Keywords: Aged; Image Processing; Computer-Assisted/Methods; Liver Cirrhosis/Diagnosis; Magnetic Resonance Imaging/Methods; Subtraction Technique; HEPATOCELLULAR-CARCINOMA; DIAGNOSIS; NODULES; MRI